A Review on Real-Time Network Traffic Monitoring and Anomaly Detection System : A Comprehensive Study with User-Friendly Interface and Historical Analysis Capabilities - Sakshi Bakhare; Dr. Sudhir W. Mohod (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Protecting the integrity and security of computer networks is crucial in an era of all-pervasive digital connectedness. The user-friendly interface and powerful historical analytical capabilities of the Real-Time Network Traffic Monitoring and Anomaly Detection System are highlighted in this review paper’s thorough investigation of the system. This technology takes the stage in a setting where conventional security measures frequently fall short against developing threats that blend in with regular network traffic. It provides experienced administrators and newcomers with real-time insights into network traffic. Additionally, its skills for historical analysis come in handy for post-incident investigations and boosting general network security. This assessment emphasizes the system’s crucial function in thwarting existing and new network threats, establishing it as a cornerstone of successful cybersecurity plans for both businesses and private citizens.